Histologic Patterns of Cutaneous Metastases of Breast Carcinoma: A Clinicopathologic Study of 232 Cases. (June 2021) - Ronen, Shira; Suster, David; Chen, Wei-Shen; Ronen, Natali; Arudra, Sri Krishna C.; Trinidad, Celestine; Ivan, Doina; Prieto, Victor G.; Suster, Saul
Abstract : Abstract: Cutaneous metastasis may be the initial sign of internal malignancy but more often represents a late manifestation of widely disseminated disease. Breast carcinoma is the most common malignancy to metastasize to the skin. Although several studies have detailed the histopathologic patterns of cutaneous metastasis from internal malignancies, very little has been published regarding metastases of breast carcinoma to the skin. Furthermore, the histopathologic and clinical features observed in the cases of breast carcinoma with local skin involvement as opposed to cases exhibiting distant cutaneous metastases have not been adequately investigated. We have reviewed 232 cases of breast carcinoma with cutaneous metastases from 2 large institutions. All cases of carcinoma of the breast with involvement of the skin of the anterior chest wall were compared with those with distant cutaneous metastases. Two hundred thirty-two cases in 199 patients were included, of which 126 had skin involvement exclusively involving the ipsilateral anterior chest, and 106 had biopsy-proven distant cutaneous metastases. Twelve patients had both local and distal spread. Distant cutaneous metastases showed a predilection for the contralateral anterior chest wall area, followed by the head and neck, back, and abdomen. Histologically, most of the tumors presented in this series showed features of infiltrating ductal carcinoma. In both ipsilateral and distant metastases, the tumors demonstrated little change in histologic features from the primary lesion; however, the distant metastases showed a tendency to display more poorly differentiated features. The mean patient survival when cutaneous involvement was localized to the skin of the anterior chest wall was 23 months as compared with 20.6 months when distant sites were affected. A comparison of the clinicopathologic features of the patients presented in this series suggests that alternate biological mechanisms may apply for local and distant skin metastases from breast carcinoma.